SENGKETA PEMBATALAN HIBAH DI PENGADILAN AGAMA STABAT DITINJAU DARI MASLAHAH - Wahyuni, Wahyuni; Fatmah, Fatmah (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2024)
This study aims to examine the considerations of religious court judges in examining and deciding grant cancellation disputes. This study will analyze the decision of the Religious Court regarding the cancellation of grants in terms of maslahah. This study uses qualitative normative legal research. While the approach used is statutory and conceptual approach. The data sources used are primary data sources consisting of decisions from the Religious Courts, compilations of Islamic law, books of civil law laws, compilations of sharia economic laws. Meanwhile, secondary sources of law consist of books of Islamic jurisprudence, law books, and scientific journal articles. The results of this study indicate that the panel of judges examining cases of disputes over the cancellation of dominant gifts applies article 35 paragraph 1, article 36 paragraph I law number 1 of 1974 concerning joint assets and article 1338 of the civil law code concerning agreements/agreement, thus ignoring Article regarding the permissibility of withdrawing the grant object even though the grant is without the approval of other heirs. Meanwhile, according to the theory of maslahah initiated by al-Ghazali that the decisions of the Religious Courts made by the panel of judges are ideally to realize the concept of maqasid sharia, namely maintenance of property and offspring. Thus, it can avoid negative impacts that will occur in family relationships, such as the relationship between parents and their heirs. However, according to Hans Kelsen's theory of justice, the considerations made by judges in deciding cases of cancellation of grants tended to be inconsistent in the application of the applicable legal system, so that according to him, the intended sense of justice had not been fully fulfilled.